THE IMPLEMENTATION OF FLIPPED CLASSROOM IN TEACHING ENGLISH FOR NURSING STUDENTS - Juliana Juliana; Afni Yan Syah (Premise: Journal of English Education and Applied Linguistics, 2021)
This research is a case study. The purpose of this study was to determine the process of implementing a flipped classroom for English course and analyse students’ perceptions of the implementation of the Flipped Classroom in teaching English for the nursing students of Nursing Academy of Kesdam Iskandar Muda Banda Aceh. The participant in this study were 50 students of Nursing Academy of Kesdam Iskandar Muda Banda Aceh in the academic year 2020/2021. They consist of 4 male students and 46 female students. Data collection methods in this study are lecturer’s observation checklist, teacher’s fieldnote and questionnaires. Lecturer's observation checklist in the form of a checklist for implementing the flipped classroom strategy at each meeting. Lecturer’s fieldnote is some notes that found while flipped classroom was implemented.  Questionnaires are used to obtain results from student opinions and student experiences in Flipped Classroom. More than half of students felt that Flipped classroom aided their English studies. Most of the students enjoyed the flipped classroom learning and believed that this method can support their learning. This implies that the method is still useful for EFL classroom of  ELT context. .